2017
DOI: 10.1098/rstb.2016.0425
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and social transmission in experimental micro-societies: exploring the scope of cumulative culture in young children

Abstract: a.whiten@st-andrews.ac.uk 2 The experimental study of cumulative culture and the innovations essential to it is a young science, with child studies so rare that the scope of cumulative cultural capacities in childhood remains largely unknown. Here we report a new experimental approach to the inherent complexity of these phenomena. Groups of 3-4 year old children were presented with an elaborate array of challenges affording the potential cumulative development of a variety of techniques to gain increasingly at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 58 publications
0
50
0
Order By: Relevance
“…A critical period in endogenizing is childhood. McGuigan and colleagues [152] review the growing literature on the significance of childhood in cumulative culture, and identify the underlying 'dual engines' as invention and copying/transmission. The authors then present a study of children in which the subjects were free to invent, rather than have adult models introduce inventions.…”
Section: (C) Transmission Selection and Construction Of Noveltymentioning
confidence: 99%
“…A critical period in endogenizing is childhood. McGuigan and colleagues [152] review the growing literature on the significance of childhood in cumulative culture, and identify the underlying 'dual engines' as invention and copying/transmission. The authors then present a study of children in which the subjects were free to invent, rather than have adult models introduce inventions.…”
Section: (C) Transmission Selection and Construction Of Noveltymentioning
confidence: 99%
“…Whiten described how in his research, better representing the complexities of the real world has been a major goal. For example, in his recent research exposing children and chimpanzees to microworlds affording cumulative cultural change, complexity is multifaceted because tools, actions, and even the decision process needed for task success, exhibit rising levels of complexity . Even researchers within the same field (animal behavior) differed in whether they considered complexity in terms of the process or the product, highlighting the divisive nature of this widely used, yet poorly defined, term.…”
Section: Panel Discussion and Emergent Themesmentioning
confidence: 99%
“…For example, in his recent research exposing children and chimpanzees to microworlds affording cumulative cultural change, complexity is multifaceted because tools, actions, and even the decision process needed for task success, exhibit rising levels of complexity. 1 Even researchers within the same field (animal behavior) differed in whether they considered complexity in terms of the process or the product, highlighting the divisive nature of this widely used, yet poorly defined, term. Caldwell (previously inspired by audience member, Dr. Mark Atkinson, University of Stirling) suggested that the term CCE could be reserved for describing the process which produces accumulated products, and the products themselves referred to as cumulative culture (CC).…”
mentioning
confidence: 99%
“…Research in child development has offered much insight into the ontogeny of cumulative culture in general (Dean, Kendal, Schapiro, Thierry, & Laland, ; Flynn & Whiten, ), and the transmission–innovation balance in particular (Legare & Nielsen, ; McGuigan et al, ; Rawlings, Flynn, & Kendal, ; Tennie, Walter, Gampe, Carpenter, & Tomasello, ). Indeed, substantial evidence has suggested that both the tendency to copy the form of an action and to copy its goal have roots early in life (Meltzoff, ; Over & Carpenter, ; Užgiris, ; Want & Harris, ).…”
Section: Introductionmentioning
confidence: 99%